Neutrophil/lymphocyte index as a prognostic predictor in patients with primary biliary cholangitis - Carlos S. Tinitana-Jumbo; Viridiana López-Ladrón-De Guevara; Karina Cazarín-Chávez; Paloma M. Diego-Salazar; Santiago Camacho-Hernández; María F. Higuera-De la Tijera (Annals of Hepatology)
Introduction and Objectives: There is an inadequate response to first line treatment in 40% of patients with primary biliary cholangitis (PBC). The neutrophil/lymphocyte (N/L) index has been associated with poor long-term prognosis. Our objective was to evaluate the relationship of N/L index with prognosis at 1 year of treatment in patients with PBC. Materials and Patients: This is an observational, retrospective, and analytical study of patients diagnosed with PBC, evaluating the prognosis according to the response to treatment measured by the GLOBE scoring system and its relationship with the N/L index at the time of diagnosis. Qualitative data are expressed as percentages and quantitative data as mean±SD. Statistical comparison was performed with the two-tailed unpaired Student´s t-test or chi-square, as appropriate. Alpha=0.005. Results: A total of 128 patients (54.21±10.26 years, 93.8% women) with PBC were included. According to the GLOBE score, 27.3% were classified as “good prognosis” and 72.7% as “poor prognosis”. The N/L index was lower in the good prognosis group (2.29±0.99) compared to the poor prognosis group (3.06±1.48, p=0.005), also the Meld-Na scoring system was higher in the poor prognosis group (11.57±4.96 vs. 7.62±1.33, p=0.005). Mortality in the population was 9.4% all belonging to the poor prognosis group.Conclusions: The N/L index in patients diagnosed with PBC is related to the prognosis after one year of treatment as measured by the GLOBE score. It is necessary to prospectively assess the findings in order to be able to determine their prognostic utility at the time of diagnosis.